A Generalization of Lindley Distribution with Properties and Application: A Generalization of Lindley Distribution with Properties and Application - Rashid, Qaisar; Yaseen, Hafiz Muhammad; Jamshaid, Muhammad Tariq (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Lifetime data analysis is an important part of the Physical sciences, Engineering, and insurance sectors. The present study proposed a generalized form of Lindley distribution, which is a lifetime model, and developed its Statistical properties including moment generating function, generalized moment function, mean deviations, Bonferroni and Lorenz curve, reliability measures (survival function, hazard function, cumulative hazard function, reversed hazard function, mean residual life function), order statistics and Reyni entropy. An application of real-life data showed that the proposed model best fitted the data.